Assessment of nutrient profile of school meal program in primary school in Kota Bharu, Kelantan - Ibrahim, Abdul Thaqif (Universiti Sains Malaysia, 2024)
The study used a non-probability sampling method, specifically convenience sampling techniques. Four schools with the school meal program were chosen at random from the 92 that met the inclusion criteria. The four primary schools selected for this study, which demonstrated different dietary patterns, are located in Kota Bharu, Kelantan. All food samples over ten school days were analyzed for calorie, protein, carbohydrate, fat, fiber, calcium, iron, and folate (Vitamin B-9) content. Most of the meals provided were rice-based, such as rice porridge, chicken rice, Chinese fried rice, villager’s fried rice, chicken curry rice, coconut milk rice, and paprika rice. The range of calories, protein, carbohydrates, and fat per serving for each school was 320-484 kcal, 13-22 g, 34-75.1 g, and 9-13.3 g. The meals provided under the Rancangan Makanan Tambahan (RMT) contained high amounts of energy and carbohydrates but low protein content. The recommended amounts of energy, protein, carbohydrates, and fat per serving for breakfast were 300-400 kcal, 25-40 g, 45-60 g, and less than 20 g for fat. The targeted nutritional intervention recommends schools enhance calcium and dietary fibre intake, as these nutrients were frequently deficient in the assessed meals, while decreasing total energy, carbohydrate, and fat, particularly in high-calorie and fatty dishes. Diversifying meal options by including more fruits, vegetables, and whole grains are suggested for school canteens, as ensures balanced macronutrient distribution with lean proteins, complex carbohydrates, and healthy fats. High-sugar and high-fat foods should be served less frequently to help control calorie intake and promote healthier eating habits.